Retinal prostheses in degenerative retinal diseases. Issue 9 (September 2015) - Lin, Tai‐Chi; Chang, Hua‐Ming; Hsu, Chih‐Chien; Hung, Kuo‐Hsuan; Chen, Yan‐Ting; Chen, Szu‐Yu; Chen, Shih‐Jen
Abstract : Abstract : Degenerative retinal diseases may lead to significant loss of vision. Age‐related macular degeneration (AMD) and retinitis pigmentosa (RP), which eventually affect the photoreceptors, are the two most common retinal degenerative diseases. Once the photoreceptorcells are lost, there are no known effective therapies for AMD or RP. The concept of retinal prosthesis is to elicit neural activity in the remaining retinal neurons by detecting light and converting it into electrical stimuli using artificial devices. Subretinal, epiretinal, and other retinal prostheses implants are currently designed to restore functional vision in retinal degenerative diseases. In this review, we have summarized different types of retinal prostheses, implant locations, and visual outcomes. Our discussions will further elucidate the results from clinical trials, and the challenges that will need to be overcome to more efficaciously assist patients with AMD and RP in the future.